Unveiling hidden threats: Molecular surveillance of bacterial and protozoan infections in Asian water monitors (Varanus salvator) at Thailand’s Khao-zon Wildlife Breeding Station - Witchuta Junsiri; Jitkamol Thanasak; Tawewan Issarankura Na Ayudhaya; Somjit Chaiwattanarungruengpaisan; Piyanan Taweethavonsawat (Current Research in Parasitology and Vector-Borne Diseases)
Asian water monitors (Varanus salvator) are often exposed to harmful microorganisms such as species of Hepatozoon, Anaplasma, Rickettsia, and Borrelia. These pathogens pose significant risks to wildlife and public health. In this study, we aimed to investigate the presence and genetic diversity of pathogenic microorganisms in V. salvator from the Khao-zon Wildlife Breeding Station, Ratchaburi, Thailand. Sixteen V. salvator were collected, and thin blood smears and polymerase chain reaction (PCR) assays of the DNA isolated from blood were used to identify infections. Blood smear analysis revealed two positive samples (2/16; 12.5%) for Hepatozoon sp. PCR results confirmed the presence of Hepatozoon sp. (6/16; 37.5%), Anaplasma sp. (3/16; 18.75%), Rickettsia sp. (2/16; 12.5%), Borrelia sp. (4/16; 25.0%) and Burkholderia sp. (1/16; 6.25%). Phylogenetic analysis revealed 99.86% similarity of Hepatozoon sp. sequences with Hepatozoon ophisauri (GenBank: MN723845) in Pseudopus apodus from Iran, whereas the gltA gene of Rickettsia sp. was closely related to Rickettsia conorii raoultii (GenBank: MF002515) in Dermacentor nuttalli from China. This study represents the first detection of the five pathogens in V. salvator from Thailand and provides valuable insights into the genetic diversity of these microorganisms. Our findings suggest that V. salvator may serve as reservoir for multiple pathogens, posing potential threats to both wildlife and humans. The presence of zoonotic agents such as Rickettsia spp., Anaplasma spp., and Borrelia spp. underscores the importance of continued surveillance in wildlife populations to mitigate the risk of emerging infectious diseases.